Social perspective of sustainable consumption, a case study for toothpaste boxes - GÜRSOY HAKSEVENLER, BETÜL HANDE (My University, 2022)
With the rapid population growth and consumption habits, the importance of waste disposal is increasing. Packaging wastes constitute a large share of these wastes. Based on the Zero Waste Regulation applied in our country, by examining the studies done in our country and the world, sorting the wastes of individuals over the toothpaste boxes selected as a sample, contribute to the economy, how they look at processes in terms of being sensitive to the environment, how they act individually, it was aimed to understand how they establish a connection between the concepts, it has been tried to gain impressions on how to contribute to the zero waste target through forward-looking statements of intent. As a result of the study, it was observed that 90.7% of the participants viewed the removal of the toothpaste boxes positively or partially. It has been understood that the level of awareness on sustainable development, sustainable economy, and circular economy is not high; It has been determined that there are deficiencies in the directing of individuals. In the light of these obtained data, inferences were tried to be made on what could be done and suggestions were presented.
Keywords: Sosyal ve Beşeri Bilimler; Siyaset Bilimi; Kamu Yönetimi; Kentleşme ve Çevre Sorunları; Çevre Mühendisliği; Çevre Bilimleri; Mühendislik ve Teknoloji; Social Sciences and Humanities; Political Science; Public Administration; Urbanization and Environmental Problems; Environmental Engineering; Environmental Sciences; Engineering and Technology; Tarım ve Çevre Bilimleri (AGE); Mühendislik, Bilişim ve Teknoloji (ENG); Sosyal Bilimler (SOC); Çevre / Ekoloji; Sosyal Bilimler Genel; ÇEVRE BİLİMLERİ; SİYASET BİLİMİ; KAMU YÖNETİMİ; Agriculture & Environment Sciences (AGE); Engineering, Computing & Technology (ENG); Social Sciences (SOC); ENVIRONMENT/ECOLOGY; SOCIAL SCIENCES, GENERAL; ENVIRONMENTAL SCIENCES; POLITICAL SCIENCE; PUBLIC ADMINISTRATION; Su Bilimi; Siyasi bilimler ve Uluslararası İlişkiler; Doğa ve Peyzaj Koruma; Çevre Bilimi (çeşitli); Sosyal Bilimler ve Beşeri Bilimler; Fizik Bilimleri; Yaşam Bilimleri; Aquatic Science; Political Science and International Relations; Nature and Landscape Conservation; Environmental Science (miscellaneous); Social Sciences & Humanities; Physical Sciences; Life Sciences